Gender and religion as factors of individual differences in musical preference. (December 2019) - Soares-Quadros Júnior, João Fortunato; Lorenzo, Oswaldo; Herrera, Lucía; Araújo Santos, Naiara Sales
The goal of this article is to analyse the musical preferences of Brazilian students by considering the variables of gender and religion. Using random sampling, a class was selected from each high school year group of 10 public schools in the city of São Luís (Brazil).The total study sample consisted of 658 students: 358 females (54.4%) and 300 males (45.6%). Of these, 343 (52.1%) were Protestants and 315 (47.9%) were Catholics, and their ages ranged from 14 to 19 years ( M = 16.24 years old, SD = 1.14). For the data collection, a version of the Questionnaire on Musical Style Preferences by Lorenzo, Herrera, and Cremades (2008) was used; however, it was shortened and culturally adapted to the Brazilian context. The participants were asked to evaluate how often they listened to 19 different styles of music. The overall results indicated that the participants' musical preferences were heavily influenced by mass media. However, ANOVA results indicated significant differences and a variety of size effects in the frequency of musical listening based on gender and religion. Females had a greater preference for styles with emotional content, dance music and music with a strong connection to mass culture, while males preferred more vigorous styles. Regarding religion, Protestants had a stronger preference for gospel music, while Catholic preferences were more diverse.